Penerapan Sistem Informasi Berbasis Database untuk Optimalisasi Pengelolaan Data Pelanggan pada Usaha Kecil - Indra Setiawan; Nur Azizah; Firman Jaya (LPPM Universitas Mulia, 2026)
Small businesses play a crucial role in the economy, most small businesses in Indonesia still rely on manual systems or applications that are not well-integrated, leading to difficulties in monitoring, analyzing, and utilizing customer data for business development. This study aims to develop and implement a database-based information system to optimize customer data management in small businesses, focusing on efficiency, accuracy, and improved data analysis. The research method used is the design and development of an information system, involving several key stages: needs analysis, system design, system development, and implementation evaluation. The needs analysis was conducted by collecting data through interviews, observations, and surveys with small business owners to understand their current data management practices and the challenges they face. The system developed uses MySQL for data storage and PHP or Python for the user interface, with main features such as customer data recording, data search, and transaction history management. The results show that the implementation of the database-based information system has significantly improved the efficiency of customer data management. The data search time, which previously took up to 180 seconds, was reduced to 30 seconds after the system was implemented. In addition, data accuracy improved due to the more structured data storage. A survey also revealed that 80% of users found the system easy to use. The discussion indicates that despite the technological limitations faced by small businesses, this system proved effective in helping manage customer data more efficiently and accurately, supporting faster and data-driven decision-making.